2011
DOI: 10.1143/jjap.50.05fb03
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial Growth of Chalcopyrite-Type CuInS2 Films on GaAs(001) Substrates by Evaporation Method with Elemental Sources

Abstract: We study quark and strange quark matter in the context of general relativity. For this purpose, we solve Einstein's field equations for quark and strange quark matter in spherical symmetric space-times. We analyze strange quark matter for the different equations of state (EOS) in the spherical symmetric space-times, thus we are able to obtain the space-time geometries of quark and strange quark matter. Also, we discuss the features of the obtained solutions. The obtained solutions are consistent with the resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…A few reports are available for the growth of other I-III-VI 2 chalcopyrite-type semiconductors. [20][21][22] Different surface phases were detected in the growth under different Cu/In ratios for CuInS 2 20) and CuInSe 2 . 21) However, no dynamic study during growth has been reported in these materials.…”
Section: Introductionmentioning
confidence: 99%
“…A few reports are available for the growth of other I-III-VI 2 chalcopyrite-type semiconductors. [20][21][22] Different surface phases were detected in the growth under different Cu/In ratios for CuInS 2 20) and CuInSe 2 . 21) However, no dynamic study during growth has been reported in these materials.…”
Section: Introductionmentioning
confidence: 99%